Gq neuromodulation of BLA parvalbumin interneurons induces burst firing and mediates fear-associated network and behavioral state transition in mice - Xin Fu; Eric Teboul; Grant L. Weiss; Pantelis Antonoudiou; Chandrashekhar D. Borkar; Jonathan P. Fadok; Jamie Maguire; Jeffrey G. Tasker (Nature Communications, 2022)
The authors study mechanisms underlying neuromodulatory control of transitions between brain and behavioral states. They identify a mechanism whereby modulation of Gq activity in basolateral amygdala parvalbumin interneurons mediates the transition to a fear-associated network and behavioral state.